A STUDY OF FINANCIAL BEHAVIOR BASED ON THEORY OF PLANNED BEHAVIOR - Patel, Priyanka; Nayak, Keyur (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of this research is to investigate the applicability of the Theory of Planned Behaviour (TPB) in assessing the behavioural intention to invest among a specific group of individuals. This construct is an expansion of the Theory of Planned Behaviour (TPB) model that considers the significance of risk tolerance as a key factor influencing the investment intentions of individuals in the community. The study also examines the role of financial literacy in moderating the association between TPB and investment aspirations. This paper employs a cross-sectional research technique. The research model was validated using the approach of structural equation modelling (SEM). This research used a survey questionnaire to collect data from 114 individuals living in Ahmedabad, the metropolitan centre with the highest population in the state of Gujarat. Further analysis of the data was conducted using Smart PLS software. The results emphasise the importance of risk tolerance and financial literacy in conjunction with the decisions that investors plan to make about their investments. The current study provides evidence that investing decision-making is significantly impacted by variables including attitude, subjective standards, perceived behavioural control, and risk tolerance. The aforementioned research demonstrate that enhancing one’s financial literacy may result in a heightened inclination to invest in financial assets. Nevertheless, the study indicates that possessing a more comprehensive knowledge of money does not mitigate the dangers linked to investing. This study extends the well- established TPB model by include risk tolerance and financial knowledge as moderators when examining behavioural intentions. Furthermore, it expands the range of TPB’s effectiveness in the domain of investment decision-making to include additional categories of financial assets.